PROFASA—a web-based protein fragment and structure analysis workstation - Mi, Yanlin; Marcu, Stefan-Bogdan; Tabirca, Sabin; Yallapragada, Venkata V. B. (Frontiers in Bioengineering and Biotechnology, 2023)
In recent years, our understanding of protein structure and function has resulted in exponential growth in various applications such as food, diagnostics, therapeutics and novel materials. Today, there is an arsenal of in silico tools available for protein modeling (Cramer, 2021), designing proteins (Walker et al., 2021) and analysis (Yallapragada et al., 2020). However, most of these tools to-date require high technical expertise to access, install and effectively use them. Current in silico tools excel at providing cutting edge computational technology but fall short in usability due to a lack of user friendly interface and complicated working protocols. As the market need for protein based applications expands, it also raises the need for a one-stop platform for in silico tools. In this article, we introduce PROFASA, a protein workstation, that aims to provide a unified platform for studying protein structure. PROFASA combines state of the art protein structure visualisation with cutting edge tools and algorithms for in silico protein analysis. Features such as real-time collaboration, note sharing, and shared projects make PROFASA a great tool for researchers and teaching professionals alike. The design, user interface, features, applications and ambitions of PROFASA are discussed in this manuscript.